Vertical stratification of a temperate forest caterpillar community in eastern North America - Seifert, Carlo L; Lamarre, Greg P A; Volf, Martin; Jorge, Leonardo R; Miller, Scott E; Wagner, David L; Anderson-Teixeira, Kristina J; Novotný, Vojtěch (Oecologia, 2020)
Vertical niche partitioning might be one of the main driving forces explaining the high diversity of forest ecosystems. However, the forest's vertical dimension has received limited investigation, especially in temperate forests. Thus, our knowledge about how communities are vertically structured remains limited for temperate forest ecosystems. In this study, we investigated the vertical structuring of an arboreal caterpillar community in a temperate deciduous forest of eastern North America. Within a 0.2-ha forest stand, all deciduous trees ≥ 5 cm diameter at breast height (DBH) were felled and systematically searched for caterpillars. Sampled caterpillars were assigned to a specific stratum (i.e. understory, midstory, or canopy) depending on their vertical position and classified into feeding guild as either exposed feeders or shelter builders (i.e. leaf rollers, leaf tiers, webbers). In total, 3892 caterpillars representing 215 species of butterflies and moths were collected and identified. While stratum had no effect on caterpillar density, feeding guild composition changed significantly with shelter-building caterpillars becoming the dominant guild in the canopy. Species richness and diversity were found to be highest in the understory and midstory and declined strongly in the canopy. Family and species composition changed significantly among the strata; understory and canopy showed the lowest similarity. Food web analyses further revealed an increasing network specialization towards the canopy, caused by an increase in specialization of the caterpillar community. In summary, our study revealed a pronounced stratification of a temperate forest caterpillar community, unveiling a distinctly different assemblage of caterpillars dwelling in the canopy stratum.
Keywords: Biodiversity; Lepidoptera; North America; stromy; ekosystém; Trees; biodiverzita; Forest canopy; lesy; Animals; Food web; Feeding guilds; Forests; Ecosystem; zvířata; Specialization; Severní Amerika